1998
DOI: 10.1021/cm980380b
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Magnetism, and Properties of Ruddlesden−Popper Calcium Manganates Prepared from Citrate Gels

Abstract: Ruddlesden-Popper (RP) phases with the formula (CaO)(CaMnO 3 ) n , where n ) 1, 2, 3, and ∞, have been prepared using the Pechini citrate gel process at temperatures as low as 900 °C under flowing oxygen. The compounds were characterized by X-ray powder diffraction, Rietveld profile analysis, thermal gravimetric analysis, iodometric titrations, Mn K-edge X-ray absorption spectroscopy, temperature-dependent magnetic susceptibility, and resistivity. Rietveld analysis shows that there is an elongation in the apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
92
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 27 publications
(59 reference statements)
15
92
0
Order By: Relevance
“…8 the temperature dependence of the magnetization under a field of 0.5 T for x = 0.55, 0.67, 0.70, 0.75, 0.80 and 1.00. The sudden decrease toward lower temperatures around 110 K at x = 1.00 corresponds to an antiferromagnetic phase transition (T N ∼ = 110 K) [15], whereas the relatively gradual suppression at x = 0.67, 0.70 and 0.75 corresponds to the COO phase transition; we confirmed that the diffuse superlattice reflections appear around the temperatures indicated by the black arrows and the intensity increases progressively with decreasing temperature. It is well known that most of COO phases of manganites exhibit structural modulations based on the MnO 6 Jahn-Teller distortions and suppression of magnetization which is ascribed to the weakened double-exchange interaction due to locarization of the e g electrons.…”
Section: Resultssupporting
confidence: 76%
“…8 the temperature dependence of the magnetization under a field of 0.5 T for x = 0.55, 0.67, 0.70, 0.75, 0.80 and 1.00. The sudden decrease toward lower temperatures around 110 K at x = 1.00 corresponds to an antiferromagnetic phase transition (T N ∼ = 110 K) [15], whereas the relatively gradual suppression at x = 0.67, 0.70 and 0.75 corresponds to the COO phase transition; we confirmed that the diffuse superlattice reflections appear around the temperatures indicated by the black arrows and the intensity increases progressively with decreasing temperature. It is well known that most of COO phases of manganites exhibit structural modulations based on the MnO 6 Jahn-Teller distortions and suppression of magnetization which is ascribed to the weakened double-exchange interaction due to locarization of the e g electrons.…”
Section: Resultssupporting
confidence: 76%
“…Activated conduction at high T has been reported for all undoped Ca n+1 Mn n O 3n+1 materials 23 , which, for n = 1, has been ascribed to small polaron hopping 24 .…”
Section: Introductionmentioning
confidence: 95%
“…For example, the layered cuprate RP phases played important roles in the discovery of hightemperature superconductivity, [3][4][5][6] and the manganese-based RP family displays insulator-to-metal and ferromagnetic transformations at low temperatures, yielding colossal magnetoresistive properties. 3,10,[13][14][15][22][23][24] The structural, transport, and magnetic properties of nickelate RP compounds have also been extensively investigated, 12,25 being of recent interest as cathode materials in solid oxide fuel cells (SOFCs). 17 Other exotic properties include p-wave superconductivity in the RP ruthenate Sr 2 RuO 4 , 16 novel insulating electronic ground states from spin-orbit-coupling in Sr 2 IrO 4 , 20,26 and noncentrosymmetry in Ca 2 IrO 4 .…”
Section: Introductionmentioning
confidence: 99%